2017
DOI: 10.1200/jco.2016.71.7397
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of a Hypofractionated Radiation Regimen for the Treatment of Localized Prostate Cancer

Abstract: Purpose Men with localized prostate cancer often are treated with external radiotherapy (RT) over 8 to 9 weeks. Hypofractionated RT is given over a shorter time with larger doses per treatment than standard RT. We hypothesized that hypofractionation versus conventional fractionation is similar in efficacy without increased toxicity. Patients and Methods We conducted a multicenter randomized noninferiority trial in intermediate-risk prostate cancer (T1 to 2a, Gleason score ≤ 6, and prostate-specific antigen [PS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
452
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 578 publications
(473 citation statements)
references
References 28 publications
15
452
1
5
Order By: Relevance
“…Hypofractionation has been widely adopted with highest utilisation in breast cancer, but recent randomised trials on both prostate cancer and glioblastoma multiforme demonstrating noninferiority should see these areas rise …”
Section: Discussionmentioning
confidence: 99%
“…Hypofractionation has been widely adopted with highest utilisation in breast cancer, but recent randomised trials on both prostate cancer and glioblastoma multiforme demonstrating noninferiority should see these areas rise …”
Section: Discussionmentioning
confidence: 99%
“…Although radiotherapy of prostate is currently practiced using standard fractionation regimens (eg, 44 fx at 1.8 Gy/fx over ~9 weeks), hypofractionation is gaining more clinical attention and momentum. Several clinical trials have found hypofractionated radiotherapy to be well‐tolerated by prostate cancer patients with no apparent differences in outcome and toxicities . Moderate hypofractionation protocols (eg, 60 Gy in 20 fx) were demonstrated as non‐inferior to conventional fractionations and were recommended to become the new standard of care for radiotherapy of localized prostate cancer …”
Section: Introductionmentioning
confidence: 99%
“…7 Based on this and other studies, [8][9] mild hypofractionation has become an accepted and increasingly adopted dose schedule at ours and many other institutions. Nonetheless, in approximately 10-25% of cases, strict rectal dose-constraints are not met, generating a concern for increased risk of late toxicities, particularly in the context of higher dose per fraction.…”
Section: Discussionmentioning
confidence: 89%